Layout Design and Product Bundling Strategy Using Overall Variability of Association Rules (OCVR) Method - Cahyono Sigit Pramudyo (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2023)
Alfazzamart is a minimarket that sells various daily needs. For several months, the number of transactions per month at Alfazzamart fluctuated. Alfazzamart owners want to achieve sales targets so that profits increase. This is a challenge for employees to determine the right product bundling strategy and product layout according to buyer behavior. Therefore, this research was conducted to provide product bundling strategies and layout suggestions based on buyer behavior. This study uses the OCVR method to determine consistent purchasing patterns in each period. Based on this method, the results of the OCVR method are used as a reference in product bundling and product layout. Data processing was carried out following CRISP-DM. Based on the findings of this study, 17 bundling packages were obtained that could be implemented. Bundling package offers can be made by placing the product on the promo shelf or by the cashier offering product bundling recommendations directly. In addition, regarding the proposed change in product layout, it can be done by bringing noodle products closer to snack and soft drink products, swapping the location of bread products with syrup, bringing wafer products closer to candy products, and bringing toy products closer to ice cream so that empty shelves can be filled with accessories.